Odpowiedź:
a)
(2x + 3)/5 = (2 - x)/3 - x
2/5x + 3/5 = 2/3 - 1/3x - x
2/5x + 1 1/3x = 2/3 - 3/5
6/15x + 1 5/15x = 10/15 - 9/15
1 11/15x = 1/15
26/15x = 1/15 /*15/26
x = 1/15 * 15/26 = 1/26
b)
(x + 1)/2 - (x - 1)/3 = 1/4
1/2x + 1/2 - 1/3x + 1/3 = 1/4
3/6x - 2/6x = 1/4 - 2/4 - 1/3
1/6x = -1/4 - 1/3 /*6
x = -3/12 - 4/12 = -7/12
c)
(4x + 7)/2 - (5x - 1)/6 = x + 5
2x + 7/2 - 5/6x + 1/6 = x + 5
1 1/6x - x = 5 - 3 1/2 - 1/6
1/6x = 5 - 3 3/6 - 1/6 /*6
x = 6(5 - 3 4/6) = 6 * 1 2/6 = 6 * 1 1/3 = 6 * 4/3 = 8
d)
(x + 5)/4 - (2x + 1)/8 = 1/2(2 - x)
1/4x + 5/4 - 1/4x - 1/8 = 1 - 1/2x
1/2x = 1 - 5/4 + 1/8 /*2
x = 2(1 - 1 2/8 + 1/8) = 2 * (-1/8) = -1/4
Szczegółowe wyjaśnienie: